2014
DOI: 10.1371/journal.pone.0112233
|View full text |Cite
|
Sign up to set email alerts
|

Metrical Presentation Boosts Implicit Learning of Artificial Grammar

Abstract: The present study investigated whether a temporal hierarchical structure favors implicit learning. An artificial pitch grammar implemented with a set of tones was presented in two different temporal contexts, notably with either a strongly metrical structure or an isochronous structure. According to the Dynamic Attending Theory, external temporal regularities can entrain internal oscillators that guide attention over time, allowing for temporal expectations that influence perception of future events. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…, the first attempt to investigate whether an internal process—such as refreshing—can benefit from temporal regularities presented during the maintenance period. Previous studies have instead focused on the effect of temporal regularities on improvement of the processing of an external event . Our findings showed that the presence of temporal regularities during maintenance enhances memory performance.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…, the first attempt to investigate whether an internal process—such as refreshing—can benefit from temporal regularities presented during the maintenance period. Previous studies have instead focused on the effect of temporal regularities on improvement of the processing of an external event . Our findings showed that the presence of temporal regularities during maintenance enhances memory performance.…”
Section: Discussionmentioning
confidence: 46%
“…More specifically, the rhythm and timing of the item presentation is crucial for memory of spoken sequences as highlighted by the enhancement of recall performance when spoken sequences of digits are regularly grouped compared to an irregular grouping . Previously observed improvement of the learning of verbal or musical material presented regularly rather than irregularly can also strengthen the proposal of a central role of temporal structures during encoding . Focusing on how the to‐be‐learned material is presented in time, the bottom‐up multiscale population oscillators (BUMP) proposed a bottom‐up mechanism to account for the role of the temporal context at encoding of items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of syntax in language and music have focused on shared resources for harmonic (musical syntax) processing, which is also organized into rule-based hierarchies. 57,77 Correlational data suggest that musician children outperform their non-musician peers on morphological rule formation 78 and detection of syntactic incongruities. 56 Future studies using random assignment to music training, and specifically investigating the improvement of rhythm skills as a mediating mechanism, are necessary to evaluate a causal influence of rhythm on grammar outcomes in children with typical and atypical language development.…”
Section: Conclusion: Mechanisms For Shared Rhythm and Grammar And Futmentioning
confidence: 99%
“…We have already pointed out that it would be worthwhile to assess different implementations of input optimization using rhyme. Another relevant parameter of input optimization that we did not manipulate systematically in our study is rhythm (see Selchenkova et al, 2014 ). Rhythm naturally accompanies rhyming and melodic structures.…”
Section: Discussionmentioning
confidence: 99%